XML web services / Wong Kok Chuan - Wong, Kok Chuan (2003)
This document describes all the development processes that have been gone through from the very early phase of feasibility study till the end of maintenance phase. First of all this document explains on the overview of the web services, why we need web services and so on. Then it states the objectives of why there are needs for web services to be implemented in FCSIT, the scope of the project, and the project planning. Next, this document lists out all the literature reviews that I have done such as the ways or techniques for information gathering, the similar systems, the architecture models, the frameworks, the languages, the platforms, the servers such as web servers and database server and the tools that can be used. In this following section, the methodology that is used to implement the system is described in details explaining the overview, the features and why I have chosen to use it. In the analysis section of this document, the functional requirements are elaborated in a very comprehensive way and coupled up with the UML diagrams. The nonfunctional requirements explain the constraints that need to be handled to produce the ideal systems. The subsequent section describes the design phase of the system. In the system design, I have broke the system into small independent services so that they are easier to be focused on, developed, tested, debug, maintained, and enhanced. Next is the implementation phase which covers a brief description on the development environment used, explanations on a few algorithms used and the coding techniques and patterns which I followed. Then, the following chapter explains about the testing phase which I have done. These involved development of test plan, the unit testing and the integration testing. After that, a lengthy chapter which is devoted for discussion about the project